Comparison of serological responses to single-dose azithromycin (2 g) versus benzathine penicillin G in the treatment of early syphilis in HIV-infected patients in an area of low prevalence of macrolide-resistant Treponema pallidum infection. (24th November 2015) - Yang, Chia-Jui; Tang, Hung-Jen; Chang, Sui-Yuan; Hsieh, Szu-Min; Lee, Kuan-Yeh; Lee, Yuan-Ti; Sheng, Wang-Huei; Yang, Shang-Ping; Hung, Chien-Ching; Chang, Shan-Chwen
Abstract: Objectives: Effectiveness of single-dose azithromycin (2 g) in the treatment of early syphilis among HIV-infected patients has rarely been evaluated in the era of combination ART. Methods: Consecutive HIV-infected patients with early syphilis, who received 2 g single-dose azithromycin or 2.4 MU benzathine penicillin G, between 2007 and 2014, were prospectively observed. Genotypic resistance to macrolides was determined in Treponema pallidum isolates identified from clinical specimens using PCR assays. Rapid plasma reagin (RPR) titres were determined at baseline and every 3 months after treatment. Primary outcome was a decline of RPR titre by ≥4-fold at 12 months after treatment. Results: During the study period, 162 HIV-infected patients with early syphilis received benzathine penicillin G and 237 patients received azithromycin. At 12 months follow-up, the serological response rate for penicillin and azithromycin groups was 61.1% and 56.5% ( P = 0.41), respectively; respective response rate was 61.1% and 65.9% ( P = 0.49) if we only included patients infected with T. pallidum not harbouring macrolide resistance in the azithromycin group. In multivariate analysis, RPR titres ≥1:32 (OR 2.56; 95% CI 1.55–4.21) and prior syphilis (OR 0.54; 95% CI 0.35–0.81) were predictors of serological response. Most common adverse effects of azithromycin included diarrhoea (52.7%), nausea (22.4%), abdominal pain (18.6%), bloating (17.7%) and lassitude/somnolence (27.4%). Conclusions: In the setting of a low prevalence of macrolide-resistant T. pallidum, 2 g single-dose azithromycin achieved a similar serological response to benzathine penicillin G in HIV-infected patients with early syphilis. Major adverse effects of azithromycin were gastrointestinal symptoms and lassitude/somnolence.